The play(er) is the thing. No-actores en documentales animados para tiempos de pandemia: The play(er) is the thing. Non actors in animated documentaries for pandemic times - ABUÍN GONZÁLEZ, Anxo (Signa: Revista de la Asociación Española de Semiótica, 2026)
El papel de la no-ficción animada en el ecosistema audiovisual actual se aborda a partir del estudio de un corpus acotado en relación con el contexto (post-) pandémico y con la especificidad del subgénero del docu-machinima: We Met in Virtual Reality (2022), Joe Hunting; Grand Theft Hamlet (2024), de Sam Crane y Pinny Grills; The Remarkable Life of Ibali (2024), de Benjamin Ree; o Knit’s Island (2024), de Ekiem Barbier, Guilhem Causse y Quentin L’Helgouac’h. La naturaleza disruptiva del medio, como ejemplo de no-mímesis fotorrealista, sirve para adentrarse en las fronteras de lo real o para desvelar las verdades ocultadas por los medios dominantes. El corpus se analiza también desde el concepto de no-actor, desnaturalizado y convertido en usuario, avatar o marioneta que cuestiona la idea misma de corporalidad o presencia y despliega todo un abanico de identidades idealizadas o performativizadas en el mundo contemporáneo. Palabras clave: Documental animado. Docu-machinima. No-actor. Avatar. Performativización. Abstract: This study addresses the role of animated non-fiction in the current audiovisual ecosystem by examining a specific corpus in relation to the (post-)pandemic context and the particularities of the docu-machinima subgenre: We Met in Virtual Reality (2022), by Joe Hunting; Grand Theft Hamlet (2024), by Sam Crane and Pinny Grills; The Remarkable Life of Ibali (2024), by Benjamin Ree; or Knit’s Island 2024), by Ekiem Barbier, Guilhem Causse, and Quentin L’Helgouac’h. The disruptive nature of the medium, as an example of photorealistic non-mimesis, serves to delve into the boundaries of the real or to unveil truths concealed by dominant media. The corpus is also analyzed through the concept of the non-actor, denaturalized and transformed into a user, avatar, or puppet, which questions the very idea of corporeality or presence and displays a range of idealized or performatized identities in the contemporary world. Keywords: Animated Documentary. Docu-machinima. Non-Actor. Avatar. Performativization.